IMPLEMENTATION OF THE SMART ABA METHOD ON TOILET TRAINING SKILLS IN CHILDREN WITH AUTISM SPECTRUM DISORDER - Rudy Sutadi; Agita Tunjungsari; Alfred Pakpahan; Arneliza Arneliza; Kuncono Teguh Yunanto (Universitas Negeri Padang, 2024)
Independent toilet skills are basic skills that must be mastered by every child, including children with autism spectrum (ASD). This skill begins with toilet training. However, toilet training for ASD children is a challenge in itself. Children with ASD have developmental disorders that impact many aspects of their lives, including toilet training skills. This study aims to determine the effectiveness of the Smart ABA (Smart Applied Behavior Analysis) Method on the toilet training ability of ASD children. Smart ABA is a development of Applied Behavior Analysis (ABA). This study uses an experimental method with a single research subject design and data analysis using visual graphs. The subjects of this study are two children with ASD, a boy aged 5 years and 7 years. The parents of the subjects were included in this study. The Smart ABA therapists who trained the subjects in this study have fulfilled their competencies as Smart ABA therapists. The most important finding of this study was the success of both subjects in daytime toilet training within 43 to 67 days. These findings show the effectiveness of the Smart ABA method in achieving independence in toilet skills for ASD children. The results of this study will provide an in-depth understanding for parents of children with ASD, therapists, professionals, and doctors in the management of toilet training. The results of this study make an important scientific contribution to independent toilet skills in children with ASD. The stages of self-toilet skills using Smart ABA are discussed.